National and international legal definition of medicinal products and innovations in the medical field - Zanevska, Iryna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
In the conditions of European integration processes, the medical field, in particular the issue of medicines and innovative medical technologies, plays an important role in social relations. In our time, it is important that the provision of high-quality and effective medicines takes place within the legal framework and is clearly defined by the current legislation of Ukraine and international legal acts, because this is one of the priority issues in the field of health and life protection of the population of Ukraine and other countries.The International Organization for Economic Cooperation and Development noted that the use of innovative medical technologies and the latest medicines in recent years stimulated progress in the treatment of many diseases and extended people's lives in European countries by 73%. Ukraine’s accession to the World Trade Organization and the signing of the Agreement with the European Union require the state to ensure a balance between the interests of drug manufacturers, innovations and their consumers.In the modern international legal space, there is no single definition of the concept of «medicine» and «innovation in medicine», which prevents the proper exchange of information and legal regulation of this issue in the legislation of various countries of the world. Therefore, it is important and urgent to determine the concept and content of medicinal products and medical innovations in order to ensure the protection of intellectual property rights in this field, the creation of a single regulatory and legal database that will contribute to the unification of the procedure for patenting, licensing and registration of medicinal products, effective interaction of authorized authorities in the fight against the distribution of falsified and low-quality medicines, counterfeits and other violations and abuses in this area.The purpose of the article is to analyze existing definitions of the concept and essence of «medicine» and «innovative technologies in the field of medicine» in domestic and foreign legislation, as well as in international legal acts, with the aim of unifying the concepts, finding the most correct recognition that corresponds to and reveals the essence and main content given concepts.